Precipitation explains GRACE water storage variability over large endorheic basins in the 21st century - Petch, Samantha; Dong, Bo; Quaife, Tristan; King, Robert P.; Haines, Keith (Frontiers in Environmental Science, 2023)
Seasonal-interannual variations in surface water storage revealed by the Gravity Recovery and Climate Experiment (GRACE) satellite have received less attention than storage trends in the literature. We focus on 6 large endorheic basins and develop variability attribution diagnostics against independent precipitation and evapotranspiration (hereafter P and E) datasets. We apply a monthly budget closure approach giving self-consistent coupled water and energy exchanges from 2002-2020. Closed energy budgets often then show interannual amplitudes which are correlated with the water budget through shared latent heat flux losses, although these have not been independently verified.On seasonal timescales P and E data show insufficient cancellation implying over-large seasonal variations in surface storage. In most basins P drives the seasonal storage cycle with E damping storage amplitudes, although in the Caspian basin seasonal storage is driven by E, with P remaining seasonally constant when integrated over the whole drainage basin. Budget closure mostly adjusts E, which has larger uncertainties, in fitting the GRACE data.On year to year and multi-year timescales there is a strong correlation between P driven storage and the observed GRACE variability, which ranges between 0.55 and 0.88 across basins and is also retained after budget closure. However storage changes driven by P alone are too large compared to GRACE, with E data from FluxCOM generally having only very weak interannual variations. After budget closure interannual E variability is substantially increased. Although water flux trends cannot be detected with significance due to the large interannual variability; the strong agreement between GRACE storage and precipitation variations, especially over the Caspian basin, lend no support to the suggestion that E changes driven by climate change are responsible for water storage trends seen by GRACE.